Impact of Polypropylene, Steel, and PVA Fibre Reinforcement on Geopolymer Composite Creep and Shrinkage Deformations - Gailitis, Rihards; Гайлітіс, Ріхардс; Sprince, Andina; Спринс, Андіна; Kozlovksis, Tomass; Козловксіс, Томас; Pakrastins, Leonids; Пакрастінс, Леонід; Volkova, Viktorija; Волкова, Вікторія Євгенівна (IOP Publishing, 2023)
For the last 40 years, there has been increased interest in geopolymer composite development and its mechanical properties. In the last decades, there have been cases when geopolymer composites have been used for civil engineering purposes, such as buildings and infrastructure projects. The main benefit of geopolymer binder usage is that it has a smaller impact on the environment than the Portland cement binder. Emissions caused by geopolymer manufacturing are at least two times less than emissions caused by Portland cement manufacturing. As geopolymer polymerization requires elevated temperature, it also has a significant moisture evaporation effect that further increases shrinkage. It can lead to increased cracking and reduced service life of the structures. Due to this concern, for long-term strain reduction, such as plastic and drying shrinkage and creep, fibre reinforcement is added to constrain the development of stresses in the material. This research aims to determine how different fibre reinforcements would impact geopolymer composites creep and shrinkage strains. Specimens for long-term property testing purposes were prepared with 1% of steel fibres, 1% polypropylene fibres (PP), 0.5% steel and 0.5% polyvinyl alcohol fibres, 5% PP fibres, and without fibres (plain geopolymer). The lowest creep strains are 5% PP fibre specimens, followed by 1% PP fibre, plain, 0.5% steel fibre and 0.5% PVA fibre, and 1% steel fibre specimens. The lowest specific creep is to 5% PP fibre reinforced specimens closely followed by 1% PP fibre followed by 0.5% steel and 0.5% PVA fibre, plain and 1% steel fibre reinforced composites. Specimens with 0.5% steel and 0.5 PVA fibre showed the highest compressive strength, followed by 1% PP fibre specimens, plain specimens, 1% steel fibre, and 5% PP fibre reinforced specimens. Only specimens with 1% PP fibre and 0.5% steel, and a 0.5% PVA fibre inclusion showed improved mechanical properties. Geopolymer concrete mix with 1% PP fibre inclusion and 0.5% steel and 0.5% PVA fibre inclusion have a 4.7% and 11.3% higher compressive strength. All the other fibre inclusion into mixes showed significant decreases in mechanical properties. За останні 40 років зріс інтерес до розробки геополімерних композитів та їх механічних властивостей. В останні десятиліття були випадки, коли геополімерні композити використовувалися для цілей цивільного будівництва, таких як будівлі та інфраструктурні проекти. Основна перевага використання геополімерного в’яжучого полягає в тому, що воно має менший вплив на навколишнє середовище, ніж в’яжуче портландцементу. Викиди, спричинені виробництвом геополімерів, принаймні вдвічі менші, ніж викиди, спричинені виробництвом портландцементу. Оскільки полімеризація геополімерів вимагає підвищеної температури, вона також має значний ефект випаровування вологи, що додатково збільшує усадку. Це може призвести до збільшення розтріскування і скорочення терміну служби конструкцій. Зважаючи на це, для тривалого зменшення деформації, наприклад, пластичної усадки, висихання та повзучості, додається волокнисте армування, щоб стримати розвиток напруг у матеріалі. Це дослідження має на меті визначити, як різні армуючі волокна впливатимуть на деформації повзучості та усадки геополімерних композитів. Зразки для довготривалого тестування властивостей готували з 1% сталевих волокон, 1% поліпропіленових волокон (PP), 0,5% сталевих і 0,5% полівінілових спиртових волокон, 5% PP волокон і без волокон (простий геополімер). Найнижчі деформації повзучості мають зразки з 5% поліпропіленового волокна, потім 1% поліпропіленового волокна, гладке, 0,5% сталевого волокна та 0,5% ПВС волокна, а також 1% сталевого волокна. Найнижчу питому повзучість мають зразки, армовані ПП волокном 5%, потім 1% ПП волокно, потім 0,5% сталь і 0,5% волокно ПВС, звичайні та 1% армовані сталевим волокном композити. Зразки з 0,5% сталевого волокна та 0,5% полівінілхлоридного волокна показали найвищу міцність на стиск, потім зразки з 1% поліпропіленовим волокном, гладкі зразки, 1% сталевого волокна та 5% армовані поліпропіленовим волокном зразки. Лише зразки з 1% поліпропіленового волокна та 0,5% сталі та 0,5% включенням ПВА волокна продемонстрували покращені механічні властивості. Геополімербетонні суміші з 1% включенням фібри PP і 0,5% включенням сталі і 0,5% включенням фібри PVA мають вищу міцність на стиск на 4,7% і 11,3%. Всі інші включення волокон до сумішей показали значне зниження механічних властивостей.
Вплив волокнистого армування з поліпропілену, сталі та ПВС на деформації повзучості та усадки геополімерного композиту
Keywords: geopolymer composites; геополімерні композити; mechanical properties; механічні властивості; development; розробка; impact on the environment; вплив на навколишнє середовище